The Effect of Hypoxic Control Mask Exercises on Some Physiological Indicators in Terms of the Sport Technology for Young Players in Volleyball - Suhad Qasem Al-Moussawi (Journal of Global Pharma Technology, 2016)
The objectives of the study was to prepare exercises using the hypoxic mask in volleyball, to identify the effect of exercises using the hypoxic control mask in some physiological indicators in terms of the sports technology of young players in volleyball, the experimental method was used in experimental design of two experimental groups with tight control in both the tribal and remote tests on a sample of (12) young players from the volleyball industry club in the sports season (2018), were deliberately selected. The sample was randomly divided into two experimental groups of equal number. The dependent variables were determined by physiological indicators (time of the anaerobic threshold, frequency of breathing during the voltage, peak oxygen during the voltage), Adopting the technology of sport by testing the physical effort with a device system (Fitmatepro), these exercises were implemented at the beginning of the main section of the training unit at a rate of (3) training modules for a period of (8) training weeks. This indicates the number of training units (24) training units. The training exercises are similar to the volleyball skill and height control. (2000-3000) meters in increments and not more than (20) minutes from the main section of the training module, so as not to constitute harm or risk to the safety of young players, and the results were processed by the system (SPSS), and concluded the researchers that training with the hypoxic mask helps young players volleyball To develop the threshold And increase the peak oxygen, and the number of times the breath during the effort, which is a training tool that can help trainers to compensate for training in the highlands or training in different circumstances, and the young players in the volleyball who train them outperform others who train without them when developing these indicators.Keywords: Hypoxic mask, Exercises, Physiological indicators and sport technology.